Sustainable Agriculture to Support SDGs Through Innovation of Organic Fertilizer from Livestock Waste - Patunah, Siti; Pradani, Zulfan Egi (Politeknik Pertanian Negeri Payakumbuh, 2024)
Sustainable agriculture plays an important role in achieving sustainable development goals (SDGs). The use of organic fertilizers is increasingly important to increase agricultural productivity that is environmentally friendly and reduce farmers' operational costs. One of the strategies that can strengthen agriculture is innovation in the use of organic fertilizers made from livestock manure. This research aims to explore the potential for organic fertilizer innovation from livestock waste in supporting sustainable agriculture and the achievement of the SDGs. This research will analyze the economic, social, and environmental benefits of using organic fertilizers, and identify the main challenges faced in its implementation The research method used is qualitative research with data collection through interviews, questionnaire distribution, and field observation. The data collected is on the income and economic growth of five farmers in Jambi City from February to July 2024. The analysis stages are carried out through primary data collection, data analysis, and interpretation of results. The study results show that using organic fertilizers can increase the productivity of farmers' crops by up to 20%. The social implications of using organic fertilizers include improving farmers' welfare through improved soil quality and higher crop yields, which directly impact income and economic stability. In addition, the use of organic fertilizers also reduces farmers' operational costs by up to 30%. This study concludes that the use of organic fertilizers is a strategic step in realizing sustainable and environmentally friendly agriculture in the future.